2021
DOI: 10.3390/antibiotics10080894
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage SRD2021 Recognizing Capsular Polysaccharide Shows Therapeutic Potential in Serotype K47 Klebsiella pneumoniae Infections

Abstract: Klebsiella pneumoniae is an opportunistic pathogen posing an urgent threat to global public health, and the capsule is necessary for K. pneumoniae infection and virulence. Phage-derived capsule depolymerases have shown great potential as antivirulence agents in treating carbapenem-resistant K. pneumoniae (CRKP) infections. However, the therapeutic potential of phages encoding depolymerases against CRKP remains poorly understood. In this study, we identified a long-tailed phage SRD2021 specific for mucoid CRKP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Only four phages have been previously described that can lyse ST11 K47 CRKP, SH-KP152226 ( 1 ), vB_KpnP_IME205 ( 11 ), SRD2021 ( 12 ), and P-KP2 ( 13 ). Among these four phages, phages SRD2021 and P-KP2 belong to the family Siphoviridae and Myoviridae , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only four phages have been previously described that can lyse ST11 K47 CRKP, SH-KP152226 ( 1 ), vB_KpnP_IME205 ( 11 ), SRD2021 ( 12 ), and P-KP2 ( 13 ). Among these four phages, phages SRD2021 and P-KP2 belong to the family Siphoviridae and Myoviridae , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Novel phages are required as the prerequisite for cocktails to overcome phage resistance during therapy. Only four phages have been reported in the literature as able to lyse ST11 K47 CRKP, SH- KP152226 ( 1 ), vB_KpnP_IME205 ( 11 ), SRD2021 ( 12 ), and P-KP2 ( 13 ). We isolated and characterized a novel phage able to lyse ST11 K47 CRKP, expanding the repertoire of phages against CRKP.…”
Section: Introductionmentioning
confidence: 99%
“…For measuring lysis activity of the phages against Salmonella strains, stationary cultures (10 8 CFU/mL) were mixed with phages or phage combination at different MOIs (multiplicities of infection) in 96-well plates and incubated at 37 °C in a standing condition. Growth curves were monitored by measuring the optical density at 600 nm (OD 600 ) at 10-min intervals for 6 h. The one-step growth curve of a phage and the frequency of phage-resistant mutants for strain ST149 were measured as described previously, with a slight modification [ 36 , 37 ]. Briefly, to determine the rate of mutation of S. Typhimurium ST149 to phages, approximately 10 8 CFU of overnight bacterial cells were infected with phages at an MOI of 1 at 37 °C, 180 rpm for 2 h, then the cultures were centrifuged and the pelleted cells were resuspended with SM buffer containing 10 8 PFU of corresponding phages.…”
Section: Methodsmentioning
confidence: 99%
“…SNP analysis of Kp21 and Kp21r revealed that insertion mutations occurred in at least two genes; cpsA, encoding putative capsular biosynthesis (30). A recent article reports a novel phage that recognizes the capsular polysaccharide of K. pneumoniae (31), and accordingly, we speculate that capsular polysaccharide is one of the factors allowing øKp_21 to adsorb to its host Kp21. We found that Myoviridae, in the phage cocktail, diminished the lawn density of Kp21r on the plates.…”
Section: Discussionmentioning
confidence: 83%